Regulation of myocardial amino acid balance in the conscious dog. - Schwartz, R G (1985)
The effects in vivo of physiologic increases in insulin and amino acids on myocardial amino acid balance were evaluated in conscious dogs. Arterial and coronary sinus concentrations of amino acids and coronary blood flow were measured during a 30-min basal and a 100-min experimental period employing three protocols: euglycemic insulin clamp (plasma insulin equaled 70 +/- 11 microU/ml, n = 6); euglycemic insulin clamp during amino acid infusion (plasma insulin equaled 89 +/- 12 microU/ml, n = 6); and suppression of insulin with somatostatin during amino acid infusion (plasma insulin equaled 15 +/- 4 microU/ml, n = 6). Basally, only leucine and isoleucine were removed significantly by myocardium (net branched chain amino acid [BCAA] uptake equaled 0.5 +/- 0.2 mumol/min), while glycine, alanine, and glutamine were released. Glutamine demonstrated the highest net myocardial production (1.6 +/- 0.2 mumol/min). No net exchange was seen for valine, phenylalanine, tyrosine, cysteine, methionine, glutamate, asparagine, serine, threonine, taurine, and aspartate. In group I, hyperinsulinemia caused a decline of all plasma amino acids except alanine; alanine balance switched from release to an uptake of 0.6 +/- 0.4 mumol/min (P less than 0.05), while the myocardial balance of other amino acids was unchanged. In group II, amino acid concentrations rose, and were accompanied by a marked rise in myocardial BCAA uptake (0.4 +/- 0.1-2.6 +/- 0.3 mumol/min, P less than 0.001). Uptake of alanine was again stimulated (0.9 +/- 0.3 mumol/min, P less than 0.01), while glutamine production was unchanged (1.3 +/- 0.4 vs. 1.6 +/- 0.3 mumol/min). In group III, there was a 4-5-fold increase in the plasma concentration of the infused amino acids, accompanied by marked stimulation in uptake of only BCAA (6.8 +/- 0.7 mumol/min). Myocardial glutamine production was unchanged (1.9 +/- 0.4-1.3 +/- 0.7 mumol/min). Within the three experimental groups there were highly significant linear correlations between myocardial uptake and arterial concentration of leucine, isoleucine, valine, and total BCAA (r = 0.98, 0.98, 0.92, and 0.97, respectively); P less than 0.001 for each). In vivo, BCAA are the principal amino acids taken up by the myocardium basally and during amino acid infusion. Plasma BCAA concentration and not insulin determines the rate of myocardial BCAA uptake. Insulin stimulates myocardial alanine uptake. Neither insulin nor amino acid infusion alters myocardial glutamine release.